PERAN GURU BIMBINGAN DAN KONSELING TERHADAP MINAT LAYANAN BIMBINGAN DAN KONSELING DI SEKOLAH KELAS VIII D SMP NEGERI 3 BANJARBARU - Anwar, kasyful; Norsa'idah, Norsa'idah (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2018)
The low interest of students in counseling and guidance services can be seen from the lack of students who come by themselves in the room for guidance and counseling. The problem examined in this study is how the active role of teacher guidance and counseling on the interest of guidance and counseling services in class VIII D of SMP Negeri 3 Banjarbaru. So the purpose of this study is to find out how much the active role of teachers is guidance and counseling on the interest of counseling and counseling services for class VIII D of SMP Negeri 3 Banjarbaru. This research method is to use Qualitative methods. The research subjects in this study amounted to ten students of class VIII D. Data collection methods in this study used, observation, interviews, and documentation. The results of this study indicate that class VIII D students in SMP Negeri 3 Banjarbaru have a pretty good interest in counseling and guidance services carried out in their schools, but these students do not take advantage of existing services because of lack of motivation or self-desire to use the service. So that the active role of teacher guidance and counseling in handling this is to provide motivation to students so that the guidance given to students has an impact on good change. Keywords : guidance and counseling services, interest